2013
DOI: 10.1136/bmjopen-2012-001802
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival benefits from progression-free survival benefits in advanced non-small-cell lung cancer: evidence from a meta-analysis of 2334 patients from 5 randomised trials

Abstract: ObjectivesTo investigate whether progression-free survival (PFS) can be considered a surrogate endpoint for overall survival (OS) in advanced non-small-cell lung cancer (NSCLC).DesignMeta-analysis of individual patient data from randomised trials.SettingFive randomised controlled trials comparing docetaxel-based chemotherapy with vinorelbine-based chemotherapy for the first-line treatment of NSCLC.Participants2331 patients with advanced NSCLC.Primary and secondary outcome measuresSurrogacy of PFS for OS was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…In this pooled analysis study of 2,838 patients from 7 randomized trials, the Copula R 2 was 0.83 34 In another meta-analysis study of 2334 NSCLC patients from 5 randomized trials, only moderate surrogacy was found with a Copula R 2 of 0.62. 35 …”
Section: Discussionmentioning
confidence: 99%
“…In this pooled analysis study of 2,838 patients from 7 randomized trials, the Copula R 2 was 0.83 34 In another meta-analysis study of 2334 NSCLC patients from 5 randomized trials, only moderate surrogacy was found with a Copula R 2 of 0.62. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Published examples estimating trial-level surrogacy using trial sub-units for analysis include: evaluation of time to progression and progression-free survival as surrogates for overall survival in advanced ovarian cancer, where centers within trials are treated as the trial unit (Buyse et al, 2000; Burzykowski et al, 2001; Molenberghs et al, 2002; Tibaldi et al, 2003; Burzykowski and Buyse, 2006); change in visual acuity at 6 months after treatment as a surrogate for change in visual acuity at 12 months in age-related macular degeneration, where centers are treated as trial units (Buyse et al, 2000; Molenberghs, Geys, and Buyse, 2001; Molenberghs et al, 2002; Tibaldi et al, 2003; Alonso et al, 2004, 2006; Pryseley et al, 2007; Abrahantes, Shkedy, and Molenberghs, 2008; Molenberghs et al, 2008); progression-free survival as a surrogate for overall survival in advanced colorectal cancer, with centers as trial units (Burzykowski et al, 2001; Molenberghs et al, 2002; Tibaldi et al, 2003; Burzykowski and Buyse, 2006; Abrahantes, Shkedy, and Molenberghs, 2008); outcomes of the Positive and Negative Syndrome Scale (PANSS) as a surrogates for the Clinician’s Global Impression (CGI) scale in schizophrenia, where treating physicians, main investigators, or countries were considered as trial-level replicates (Molenberghs et al, 2002; Renard et al, 2002; Alonso et al, 2002, 2003, 2004b, 2006; Tilahun et al, 2007; Alonso and Molenberghs, 2007; Abrahantes, Shkedy, and Molenberghs, 2008; Molenberghs et al, 2008, 2010); prostate specific antigen (PSA) as a surrogate for overall survival in advanced prostate cancer, where country was used as the trial unit (Renard et al, 2003; Molenberghs et al, 2004); recurrence-free survival as a surrogate for overall survival in colon cancer, with grouped centers treated as the trial unit(Sertdemir and Burgut, 2009); leukemia-free survival as a surrogate for overall survival in maintenance therapy trials for patients with acute myeloid leukemia in complete remission, where countries within a single trial were treated similarly to trials Buyse et al (2011); pathologic complete response and local control as surrogates for overall survival in advanced rectal cancer, where grouped centers were treated as trial units Bonnetain et al (2012);and progression-free survival as a surrogate for overall survival in advanced non-small-cell lung cancer, where centers within trials was the unit of assessment of trial-level surrogacy Laporte et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Its use in superiority trials is debated namely due to its subjectivity, to the influence of the intervals between assessments and to the lack of impact on survival in the case of small benefits [33]. The impact of a noninferior progression-free survival on overall survival should be further studied using retrospective studies as it has been shown that, in the population of patients with advanced NSCLC, large benefits are needed in progression-free survival to warrant a (small) benefit in survival [33]. This justifies the need to study the impact on survival of a noninferior outcome in progression-free survival.…”
Section: Discussionmentioning
confidence: 99%